2(-35-7+5)=-4(a+4)

Simple and best practice solution for 2(-35-7+5)=-4(a+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-35-7+5)=-4(a+4) equation:



2(-35-7+5)=-4(a+4)
We move all terms to the left:
2(-35-7+5)-(-4(a+4))=0
We add all the numbers together, and all the variables
-(-4(a+4))+2(-37)=0
We add all the numbers together, and all the variables
-(-4(a+4))-74=0
We calculate terms in parentheses: -(-4(a+4)), so:
-4(a+4)
We multiply parentheses
-4a-16
Back to the equation:
-(-4a-16)
We get rid of parentheses
4a+16-74=0
We add all the numbers together, and all the variables
4a-58=0
We move all terms containing a to the left, all other terms to the right
4a=58
a=58/4
a=14+1/2

See similar equations:

| w3=47 | | 2/9x-1/3=10 | | 2•x+8=90 | | 2/9x+1/3=10 | | 2*x+x/2=132 | | -12+x=12-14x | | 7r-5r+4=7r-r | | 15=v+2v | | 48=14w-8w | | 35+x=3x-10 | | x+2=2+4x | | 3/5x-1=-4 | | 3x-6=-10x+7 | | 2p+1.1=64 | | -56x−2=−5 | | 2(2x+11)=-34 | | 2w^2+3-35=0 | | -8-1/2x=9 | | 1.05+x=1.0 | | -8(x-5)=-9(6-x) | | 27=10u-I | | x-(x*0.08)=150000 | | 6f-12=(-4f+6) | | -5(3y-3)-y=-3(y-3) | | -5(2x-4)-x=-4(x-3) | | -19=9t | | 6.4u-5.1u=(-3.25) | | F(x)=15x-6 | | 5x+7=3x+29. | | 3(n−8)=12+2n | | X+72+x+122=180 | | 3u=u=2-13 |

Equations solver categories